2017
DOI: 10.2185/jrm.2932
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study on the risk assessment of newly certificated long-term care need of elderly individuals in a community: Basic checklist and specific health checkup

Abstract: Objective: This study aimed to examine the factors influencing the requirement of a certificate of long-term care using a basic checklist and items listed in the Special Health Checkup.Method: This study included 7,820 individuals living in Uji city, who were selected from among 8,000 elderly individuals who, in 2008, underwent a specific health checkup (hereafter referred to as the ‘specific health checkup for the old-old elderly individuals’) for those aged 75 years and above. They answered questions from ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In previous studies, the odds ratios of the KCL items over one year with respect to Certification were 1.25-2.71 15,16) , while the proportional HRs were 1.13-2.26 13,14) . The present study differs from previous studies since it identifies changes over a three-year period, with a subsequent twoyear follow-up on the incidence of new LTCI Certifications.…”
Section: Relationship Between Change In Each Kcl Item and New Certificationmentioning
confidence: 83%
See 1 more Smart Citation
“…In previous studies, the odds ratios of the KCL items over one year with respect to Certification were 1.25-2.71 15,16) , while the proportional HRs were 1.13-2.26 13,14) . The present study differs from previous studies since it identifies changes over a three-year period, with a subsequent twoyear follow-up on the incidence of new LTCI Certifications.…”
Section: Relationship Between Change In Each Kcl Item and New Certificationmentioning
confidence: 83%
“…Recent systematic reviews identified the KCL as a reliable tool for predicting aspects of frailty, including elders’ overall vulnerability and functional disorders, Instrumental Activities of Daily Living (IADL) limitations, and sadness/depression 11 ) . Previous longitudinal studies investigated the correlations between KCL items and Certification over one year using “response/no response” to the KCL items 12 ) , with individual items as the independent variable 13 ) . Meanwhile, other longitudinal studies that investigated the correlation between KCL items and Certification over one year used individual dimensions 14 , 15 , 16 ) and total score 17 ) as the independent variable.…”
Section: Introductionmentioning
confidence: 99%
“…Satake et al found that KCL classification of physical frailty status could be a significant tool to predict the 3-year risk of functional disability [ 99 ]. Katsura et al showed that many, but not all, items were significantly associated with a 5-year risk of functional disability among both the young-old and old-old [ 100 ]. Shinkai et al validated the checklist against the original version for screening high-risk older adults [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that disability is associated with the risk of mortality in older people 21 ; in particular, a decrease in the normal walking speed in older people is associated with poor life expectancy. 22 A longitudinal study of risk factors among older people in the community reported that liver dysfunction is a risk factor for the need for nursing care, 23 and CLD is known to cause more disability and limitations in ADL than osteoarthritis, heart disease, and diabetes. 6 As the number of older patients with CLD has been increasing in recent years, further measures are imperative to increase the healthy life expectancy and reduce the burden of nursing care.…”
Section: Discussionmentioning
confidence: 99%